2019
DOI: 10.22454/fammed.2018.652014
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Successful Research Departments

Abstract: Background and Objectives: Inadequate resources have led to family medicine research divisions at varying stages of development. The purpose of this analysis was to identify the factors that family medicine research “bright spot” departments perceive to be crucial to their success. Methods: In this qualitative analysis, we identified bright spot dimensions and used a snowball sampling approach to identify medical school-based departments considered to be research bright spots. With 16 leaders from eight depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…We found that a high impact research program requires strong support for research from leadership, thematic areas of research to attract donor funding, mentorship, fostering of local, national, and international collaborations, methodological and infrastructure support, and research training and capacity building. These ndings are consistent with previous studies that have explored factors associated with successful primary care research programs and research productivity (14,(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that a high impact research program requires strong support for research from leadership, thematic areas of research to attract donor funding, mentorship, fostering of local, national, and international collaborations, methodological and infrastructure support, and research training and capacity building. These ndings are consistent with previous studies that have explored factors associated with successful primary care research programs and research productivity (14,(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 91%
“…A signi cant strength of this project includes the framing of the analysis using a socioecological theoretical model (17) that allowed for the examination the primary care research enterprise at three levels of in uence including at the macro level not previously explored by other theoretical/conceptual frameworks (31)(32)(33). Another strength was the inclusion of perspectives from a broad range of key informants including several international informants.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Not all residencies will have access to such mentors, as has been seen in the limited number of bright spots of family medicine. 3 Nonetheless, we must develop this tribe of mentors. Whether in person or virtually, we must coalesce to create experiences that will allow residents full exposure to a research-based primary care future.…”
Section: Mentors and Role Modelsmentioning
confidence: 99%
“…Our findings also suggest that at least some of the research capacity variation may be due to variation in infrastructure features, which also mirrors the conclusions of several prior studies of the variation in research productivity among academic medicine departments. 11,18 Larger departments are more likely located within institutions with more research infrastructure, while smaller departments are located within institutions that are less able to invest in research. In our analysis of the middle 50% of departments by size, few features reached statistical significance for In line with previous suggestions that CTSAs offer an avenue to increase family medicine research, 23 our findings demonstrate that aligning with a CTSA was associated with a climb on the scale.…”
Section: Discussionmentioning
confidence: 99%
“…Within the specialty of family medicine, few departments have highly productive research programs. 10,11,18 The differences between highly productive family medicine departments and less productive departments have been previously described. 11,19 Potential mechanisms for increasing family medicine departmental research productivity include increasing protected faculty time, creating access to expertise in statistics or grant preparation, and developing interdisciplinary research teams.…”
Section: Introductionmentioning
confidence: 97%